Learning for uncertainty teaching students how to thrive in a rapidly evolving world - McDiarmid, G. Williamson; Zhao, Yong 1965- (Routledge, Taylor & Francis Group, 2022)
"Learning for Uncertainty explores technology's role on education, specifically unpacking the question: how should educators prepare today's children for a world that has yet to be made? As technology evolves faster than our capacity to fully understand the social, cultural, economic, and moral implications of many innovations, today's educators are tasked with the unique role of preparing students to capitalize on technology's opportunities and also mitigate its dangers to their society, to democratic processes, and to institutions. Veteran educators McDiarmid and Zhao explore the implications of emerging technologies for future jobs, organizations, students, and learning, covering topics such as: The future of work and workers as technology eliminates some industries while creating new ones. Potential futures, both bright and dark, awaiting students. The qualities, dispositions, social behaviors, and skills that are likely to advantage students in the future.
Keywords: Education / Effect of technological innovations on; Education / Aims and objectives; Éducation / Effets des innovations sur